A Phase 2b Study to Evaluate the Safety and Efficacy of VRC01 Broadly Neutralizing Monoclonal Antibody in Reducing Acquisition of HIV-1 Infection in Women in Sub-Saharan Africa: Baseline Findings. (1st May 2021) - Mgodi, Nyaradzo M.; Takuva, Simbarashe; Edupuganti, Srilatha; Karuna, Shelly; Andrew, Philip; Lazarus, Erica; Garnett, Precious; Shava, Emily; Mukwekwerere, Pamela G.; Kochar, Nidhi; Marshall, Kyle; Rudnicki, Erika; et al.
Abstract : Background: HIV Vaccine Trials Network 703/HIV Prevention Trials Network 081 is a phase 2b randomized, double-blind, placebo-controlled trial to assess the safety and efficacy of passively infused monoclonal antibody VRC01 in preventing HIV acquisition in heterosexual women between the ages of 18 and 50 years at risk of HIV. Participants were enrolled at 20 sites in Botswana, Kenya, Malawi, Mozambique, South Africa, Tanzania, and Zimbabwe. It is one of the 2 Antibody Mediated Prevention efficacy trials, with HIV Vaccine Trials Network 704/HIV Prevention Trials Network 085, evaluating VRC01 for HIV prevention. Methods: Intense community engagement was used to optimize participant recruitment and retention. Participants were randomly assigned to receive intravenous VRC01 10 mg/kg, VRC01 30 mg/kg, or placebo in a 1:1:1 ratio. Infusions were given every 8 weeks with a total of 10 infusions and 104 weeks of follow-up after the first infusion. Results: Between May 2016 and September 2018, 1924 women from sub-Saharan Africa were enrolled. The median age was 26 years (interquartile range: 22–30), and 98.9% were Black. Sexually transmitted infection prevalence at enrollment included chlamydia (16.9%), trichomonas (7.2%), gonorrhea (5.7%), and syphilis (2.2%). External condoms (83.2%) and injectable contraceptives (61.1%) were the methods of contraception most frequently used by participants. In total, through April 3, 2020, 38, 490 clinic visits were completed with a retention rate of 96% and 16, 807 infusions administered with an adherence rate of 98%. Conclusions: This proof-of-concept, large-scale monoclonal antibody study demonstrates the feasibility of conducting complex trials involving intravenous infusions in high incidence populations in sub-Saharan Africa. Abstract : Supplemental Digital Content is Available in the Text.